The influence of Pb vacancies on the properties of PZT-type ceramic transducers - SUROWIAK, Z.; KOZIELSKI, L.; WODECKA-DUŚ, B.; FESENKO, E.G.; RAZUMOVSKAYA, O.N.; REZNICHENKO, L.A.; ZAKHARCHENKO, I.N. (Archives of Acoustics, 2000)
This article is dedicated to prof. J. Ranachowski The result of investigations of the influence of lead vacancies on the crystalline structure of PZT-type ceramic piezoelectric materials is presented. The solid solution of [...] characterized by the perovskite-type structure (ABO3), is the basis of those materials. The lead vacancies (VPb) was originated by a thermal treatment. Investigations of the influence of the lead deficiency on the crystalline structure of PZT-type ceramics have been performed for solid solutions characterized by compositions corresponding to the tetragonal or rhombohedral boundary of the morphotropic region (PCR-1, PCR-8: Piezoelectric Ceramics of Rostov) and to tetragonal phase region compositions (ceramics of Pb1-x(Zr0.39Ti0.59W0.01Cd0.01) O3). It has been found that the deficiency in lead causes a reconstruction of the perovskite phase crystalline structure or a change of the elementary cell parameters of that phase. The solid solutions on the basis of Pb(Zr,Ti)O3 resolve themselves into PbTiO3, ZrO2 and PbO when the lead deficiency caused by thermal treatment increases.